Analisis Kebutuhan History Maps Sebagai Alat Pembelajaran Sejarah di SMA - Lestari, Citra Pingkan; Hastuti, Hera (Jurusan Sejarah FIS UNP, 2023)
Abstract This research aims to analyze the needs of developing a history learning media in high school for students of class X Phase E. This research is a Research and Development (R&D) research using the ADDIE model which consists of five stages namely Analysis, Design, Development, Implementation and Evaluation. However, this research only reached the analysis stage, namely: teacher analysis, student needs analysis, and curriculum analysis. Interviews and observations are the methods used for data collection in this study. This research was conducted in three phases of analysis, namely data reduction, data presentation, and drawing conclusions. Furthermore, the results of the needs analysis research are as follows: (1) student needs analysis; students need innovative media; (2) teacher analysis; and (3) curriculum analysis...: CP, ATP, and TP of history learning in accordance with History Maps. The conclusion obtained is History Maps as a new innovation of history learning media in high school. Keywords: Need Analysis, History Learning, Research and Development, History Maps Abstrak Penelitian ini bertujuan untuk analisis kebutuhan pengembangan sebuah media pembelajaran sejarah di SMA bagi siswa kelas X Fase E. Penelitian ini merupakan penelitian Research and Development (R&D) dengan menggunakan model ADDIE yang terdiri dari lima tahap yaitu Analisi, Desain, Pengembangan, Implementasi dan Evaluasi. Namun tahap yang dilakukan penelitian ini baru sampai pada tahap analisis yaitu : analisis guru, analisis kebutuhan siswa, dan analisis kurikulum. Wawancara dan observasi merupakan metode yang digunakan untuk pengumpulan data dalam penelitian ini. Penelitian ini dilakukan dalam tiga fase analisis ialah reduksi data, penyampaian data, dan menarik kesimpulan. Selanjutnya hasil penelitian analisis kebutuhan adalah sebagai berikut: (1) analisis kebutuhan siswa; siswa membutuhkan media inovatif; (2) analisis guru; dan (3) analisis kurikulum.: CP, ATP, dan TP pembelajaran sejarah yang sesuai pada History Maps. Kesimpulan yang diperoleh yaitu History Maps sebagai inofasi baru media pembelajaran sejarah di SMA. Kata Kunci : Analsisi Kebutuhan, Pembelajaran Sejarah, Research and Development, History Maps